The Influence of Inflation, Exchange Rates, World Oil Prices and World Gold Prices on the Indonesian Sharia Stock Index - Fauzan Fahmi Hasibuan; Andri Soemitra; Rahmat Daim Harahap (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to examine inflation, exchange rates, world oil prices and world gold prices against the Indonesian Sharia Stock Index for the 2017-2021 period. The method used in this study is the historical method which is distributive causal in nature, meaning that research is conducted to analyze a past situation and indicate the direction of the relationship between variables. The data collection technique used is documentation taken through online data files from the internet. The data used in this study is secondary data in which the data is obtained indirectly from statistical data and published data. Data analysis used multiple linear regression analysis. The results of the study show that the variables Inflation, Exchange Rates, World Oil Prices, World Gold Prices simultaneously have an influence on the Indonesian Sharia Stock Index. It can be seen that the calculated F value (97.929) > F table (2.54) and a significance value of 0.000 <0.05. So it can be concluded that Inflation, Exchange Rates, World Oil Prices and World Gold Prices simultaneously (together) have a significant effect on the Indonesian Sharia Stock Index. In addition, from the results of the determination test, the calculated R2 coefficient (determination coefficient) is 0.855 (85.5%).